The Physical Mechanisms Behind the Change in the Precipitation Recycling Rate in the Mid- and Lower Reaches of the Yangtze River - Guo, Wen-Kang; Wang, Xi-Yu; Gao, Wang-Ze; Yong, Jia-Hua; Bao, Xin-Yue; Wu, Yong-Ping; Feng, Guo-Lin; Dong, Wen-Jie (Frontiers in Physics, 2021)
The precipitation recycling rate (PRR) is an important index when trying to understand the physical mechanisms behind the effects of different sources of water vapor on regional precipitation. We studied the change in the PRR in the mid- and lower reaches of the Yangtze River (MLRYR), the correlation between the PRR and the external source of water vapor and local evaporation, and the possible reasons for the interannual variation of the PRR. Our study was based on an evaluation model of the PRR and used precipitation data from meteorological stations in China and NCEP/NCAR reanalysis datasets. Our results show that the mean PRR in the MLRYR for the time period 1961–2017 was largest in autumn (about 0.3) and smallest in summer (about 0.23), with a clear upward trend (passed the 95% significance F-test), except in summer. The highest trend coefficient of the PRR was in autumn (0.38), indicating that the contribution of an external source of water vapor to local precipitation was reduced. The PRR of the MLRYR was strongly correlated with the input of water vapor through the western and southern boundaries. Water vapor was mainly sourced from the Northwest Pacific Ocean, the South China Sea and the Bay of Bengal. The anomalous Northwest Pacific cyclone induced by the Pacific sea surface temperature restrained the input of water vapor into the MLRYR from the Western Pacific, the South China Sea and the Bay of Bengal, contributing to the upward trend in the PRR. We suggest that increases in the sea surface temperature in the Pacific Ocean, South China Sea and especially the Indian Ocean will have an important impact on precipitation in East Asia.